Participation and performance: decentralised planning and implementation in Ethiopia - Snyder, Katherine A.; Ludi, Eva; Cullen, Beth; Tucker, Josephine; Zeleke, Alemayehu B; Duncan, Alan J. (Wiley, 2014)
This article discusses how decentralisation policies are enacted in the planning and implementation of natural resource management interventions in rural Ethiopia. A key element of decentralisation policy is the emphasis on greater participation by local communities. Drawing on qualitative research conducted with government staff and farmers, this paper illustrates how different actors perceive and implement national policy and how these actions affect the longer‐term sustainability of land management interventions. Copyright © 2014 John Wiley & Sons, Ltd.